O1-S01.05 Estimating the rate of annual chlamydia screening uptake in US women. (10th July 2011) - Heijne, J; Althaus, C; Herzog, S; Tao, G; Kent, C; Low, N
Abstract : Background: Annual chlamydia testing of all sexually active women aged 25 years and under followed by a repeated test 3 months after treatment is recommended by the US Centers for Disease Control and Prevention (CDC) guidelines. Data from the Healthcare Effectiveness Data and Information Set (HEDIS) estimate chlamydia test coverage at about 40% per year in the last 5 years. We used empirical data and mathematical models to determine whether observed patterns of chlamydia testing are consistent with CDC guidelines and with actual trends in chlamydia prevalence in US women aged 15–25 years. Methods: First, published data from women enrolled in commercial health plans from 2002 to 2006 (n=1 985 920) were used to estimate the annual chlamydia testing rate in women aged 15–25. Second, trends in chlamydia prevalence in the same age group were studied using data from 1999/2000 to 2007/2008 (n∼600 each round) from the US National Health and Nutrition Examination Survey (NHANES). We used a Susceptible-Infected-Recovered-Susceptible (SIRS) model to estimate the annual screening rate that fit the chlamydia prevalence data best. The model described a closed population with behavioural parameters reflecting people aged 15–25 years. It explicitly incorporated sexual partnerships and took into account re-infection. Finally, the model was used to examine the effect of repeated chlamydia testing 3 months after treatment on chlamydia prevalence and to calculate repeat infection rates. Results: The estimated rate at which women are tested for chlamydia ranges from 0.06 to 0.11 per year, which corresponds to a chlamydia test every 9 to 16 years on average and an annual coverage of roughly 10%. We found no statistical evidence that chlamydia prevalence changed between 1999 and 2008 in sexually active women aged 15–25 years taking part in NHANES. Predictions from the model of the impact of screening at a rate of 0.11 per year were consistent with the observed stable chlamydia prevalence. Repeat chlamydia testing 3 months after treatment at the estimated screening level hardly influenced population prevalence. The percentage of women with a repeat infection was highest 3.8 months after treatment. Conclusion: Our study demonstrates the challenges of implementing chlamydia screening. This study suggests that low rates of chlamydia testing in the US have not reduced population chlamydia prevalence substantially.